2017
DOI: 10.3945/an.115.011130
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Novel Lipokine Palmitoleic Acid in Health and Disease

Abstract: The monounsaturated fatty acid palmitoleate (palmitoleic acid) is one of the most abundant fatty acids in serum and tissues, particularly adipose tissue and liver. Its endogenous production by stearoyl-CoA desaturase 1 gives rise to its cis isoform, cis-palmitoleate. Although trans-palmitoleate is also synthesized in humans, it is mainly found as an exogenous source in ruminant fat and dairy products. Recently, palmitoleate was considered to be a lipokine based on evidence demonstrating its release from adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(165 citation statements)
references
References 123 publications
7
152
1
5
Order By: Relevance
“…Palmitoleic fatty acid is a MUFA and its content in the liver is kept low due to its higher β‐oxidation rates compared to the oleic acid . Recently, substantial evidence emerged that palmitoleate could be considered as a lipokine . Moreover, palmitoleic acid content in tissue strongly responds to Δ9D expression with a decrease in IDDM, and an increase during metabolic syndrome, which makes it an interesting biomarker in metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitoleic fatty acid is a MUFA and its content in the liver is kept low due to its higher β‐oxidation rates compared to the oleic acid . Recently, substantial evidence emerged that palmitoleate could be considered as a lipokine . Moreover, palmitoleic acid content in tissue strongly responds to Δ9D expression with a decrease in IDDM, and an increase during metabolic syndrome, which makes it an interesting biomarker in metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in cultured hepatocytes and mouse models of diet-induced obesity suggest that palmitoleic acid has anti-inflammatory and insulin-sensitizing effects [60]. Moreover, both in vitro and in vivo studies have demonstrated that palmitoleic acid can decrease the level of pro-inflammatory mediators and reduce the level of C-reactive protein in mice [21,23]. These anti-inflammatory effects may also contribute to the neuro-protective effect of 4-2A in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, oleic acid, which belongs to n -9 MUFAs, has been found to modulate mitochondrial dysfunction, insulin resistance and inflammatory signaling [17,18,19] and act as neurotrophic factors for neurons [20]. Palmitoleic acid, a naturally occurring 16-carbon n -7 MUFA, and one of the most abundant fatty acids in the serum and tissues, was considered to be a lipokine and has been found to benefit some physiological function, such as regulating cell proliferation, and decreasing the expression of pro-inflammatory mediators and adipokines [21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…Palmitoleate concentrations in serum do seem to correlate with insulin sensitivity, but they also correlate with abdominal obesity and certain types of cancer, with unclear effects on cardiovascular health and hepatic steatosis [21]. Many of these epidemiologic studies are obscured by various forms and sources of palmitoleate present in the serum.…”
Section: Palmitoleic Acidmentioning
confidence: 98%